Eukaryotic translation initiation factor EIF3H potentiates gastric carcinoma cell proliferation. (August 2018) - Wang, Xudong; Wang, Haizhu; Zhao, Shutao; Sun, Pengda; Wen, Dacheng; Liu, Tianzhou; Liu, Hao; Yang, Zecheng; Ma, Zhiming
Graphical abstract: Highlights: The role of EIF3H in gastric carcinoma (GC) was investigated in human GC cell lines. Alterations in the EIF3H gene were found and EIF3H was overexpressed in GC samples. EIF3H knockdown suppressed GC cell proliferation and colony formation. Loss of EIF3H led to cell cycle arrest at G0/G1 phase and apoptosis. Abstract: Eukaryotic translation initiation factor 3 subunit H ( EIF3H) is required for the progression of several types of cancer. However, little is known about the function of EIF3H in gastric carcinoma. To address this issue, in the present study, we investigated EIF3H genetic alterations in and expression of EIF3H in gastric cancer tissue samples using cBioPortal and Oncomine databases. Endogenous EIF3H expression was knocked down in MGC80-3 and AGS gastric cancer cell lines by lentivirus-mediated RNA interference. We confirmed the knockdown efficiency by quantitative real-time PCR and western blotting and evaluated the effects of EIF3H silencing on cell proliferation of gastric cancer with the cell viability and colony formation assays and by flow cytometry. The OncoPrint of EIF3H generated using cBioPortal indicated that EIF3H genetic alterations (mutation, deletion and amplification) were present in two gastric cancer sample sets. The Oncomine analysis revealed that EIF3H mRNA level was upregulated in gastric cancer tissues. EIF3H knockdown inhibited cell proliferation and colony formation in gastric cancer lines and led to cell cycle arrest at the G0/G1 phase, while inducing apoptosis via up- and downregulation of pro- and anti-apoptotic factors, respectively. These results indicate that EIF3H can serve as a novel therapeutic target for the clinical treatment of gastric cancer.